STRATEGIC DRIVERS OF EMPLOYEE PERFORMANCE: ENVIRONMENT, CULTURE, AND SATISFACTION IN TEXTILE INDUSTRY - Anggraini Soemadi; Humairoh Humairoh; Fajar Maulana (Universitas Muhammadiyah Tangerang, 2026)
The urgency of this research is based on the high productivity pressures in the textile industry sector post-economic recovery, which demands the optimization of employee performance amid the risk of extreme physical work environments. The purpose of the study was to analyze the integrative influence of the work environment, organizational culture, and job satisfaction on employee performance at PT Indonesia Synthetic Textile Mills. The study used a causal-associative quantitative approach involving 83 respondents who were selected through a simple random sampling technique. Data analysis was performed using multiple linear regression with the help of SPSS Software Version 27. The results showed that partially and simultaneously, the three independent variables had a positive and significant effect on performance, with job satisfaction as the most dominant determinant. Overall, this model is able to explain 61% of employee performance variances. This research contribution provides strategic guidance for manufacturing management in formulating retention and productivity policies based on psychological well-being. The novelty of the research lies in the testing of integrative models that combine physical, normative, and emotional aspects simultaneously in labor-intensive industries in the buffer region of the capital, providing a new perspective for the validation of human resource management theories in the context of dynamic local industries.